Psychotic Episode Induced by St. John's Wort (Hypericum Perforatum): A Case Report - Gurok, Mehmet Gurkan; Mermi, Osman; Kilic, Faruk; Canan, Fatih; Kuloglu, Murat (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2014)
There is an increase in the use of herbal therapies in recent years. St. John's Wort (SJW), which is also named as Hypericum perforatum, is one of the most frequently used herbal agents in the treatment of psychiatric disorders. SJW has been shown to be efficacious in treating mild to moderate depression, insomnia, and anxiety disorders. Although exact mechanism of action is not completely understood, its active components are suggested to have antidepressant properties. Despite its beneficial therapeutic effects, SJW can also cause unexpected adverse effects. Herein, we present the case of a 47-year-old, previously healthy female who developed psychosis after taking SJW extract and successfully treated with antipsychotic therapy.
Keywords: herbal therapy; psychosis; St. John's wort